The interaction of polymorphisms of IL10 and DBH was associated with general symptoms of PANSS with TD in Chinese Han schizophrenic patients. - Hongqiang Sun; Fan Wang; Hongzhen Fan; Quanzhi Yan; Kaiyan Cui; Wei Yuan; Fushuai Zhao; Lili Zhao; Jie Yuan; Fude Yang; Thomas R Kosten; Xiang Yang Zhang (PLoS ONE)
Objective Tardive dyskinesia (TD) is a human hyperkinetic movement disorder as a result of potentially irreversible long-term chronic first-generation antipsychotic medications. Unfortunately, mechanisms involved in the development of TD have been poorly understood. Previous studies have indicated that some genetic polymorphisms of immune system and dopamine beta-hydroxylase (DBH) genes may be involved in the pathogenesis of TD. Rs1800872 and rs72393728 are located on the promoter of interleukin-10 (IL10) and DBH gene, respectively. The genetic association between the rs1800872 and TD is unclear. Previous studies have indicated that genetic variations of IL 10 and DBH are implicated in the positive and negative symptoms in schizophrenia. However, the interaction of two variations with severity of TD and symptoms of schizophrenic patients with TD has not been reported. The present study investigated whether these variations and their interaction were associated with clinical phenotypes of TD with schizophrenia in a genetically homogeneous northern Chinese Han population. Methods Rs1800872 and rs72393728 were genotyped in schizophrenic patients with TD (n = 372) and without TD (NTD; n = 412). The Abnormal Involuntary Movement Scale (AIMS) and Positive and Negative Syndrome Scale (PANSS) were applied to assess the severity of TD and psychopathology of schizophrenia, respectively. Results The allele and genotype frequencies of rs1800872 and rs72393728 did not significantly differ between TD and NTD patients (p>0.05). No significant difference was found in the AIMS total score among the genotypes of two loci (p>0.05). Interestingly, the interaction of rs1800872 and rs72393728 showed a significant association with the PANSS general score (p = 0.011), and a trend toward to the PANSS total score (p = 0.055). Conclusion These findings suggest that the interaction of rs1800872 and rs72393728 variants may play a role in psychopathology of the general symptoms on PANSS in schizophrenic patients with TD in a northern Chinese Han population.